113 Effects of Maternal Parity and Prebiotics on the Microbiome of Nursery Pigs. (12th April 2022) - Law, Kayla; Garcia, Eduardo Rosa Medina; Hastad, Chad W; Murray, Deborah; Urriola, Pedro E; Gomez, Andres
Abstract: The objective of this study was to investigate the effect of maternal parity on sow and offspring microbiomes, and the influence of parity on pig fecal microbiome and performance in response to a prebiotic post-weaning. Fecal and vaginal swabs were collected from 22 primiparous and 74 multiparous sows in a commercial farm at weaning. Fecal swabs were also collected from 48 randomly selected piglets (n = 24, from primiparous and multiparous sows respectively) at d 0, 21, and 42 post-weaning. At weaning, piglets were allotted into 3 dietary treatment groups: a standard nursery diet including pharmacological doses of Zn and Cu (CTRL), a group fed a commercial prebiotic only (PRE), and a group fed the prebiotic plus Zn and Cu (PRE+ZnCu). Extracted DNA was sequenced on the MiSeq platform targeting the V4 variable region of the 16S rRNA bacterial gene, and sequence data were analyzed using DADA2 plus various packages within the R statistical software. Although there were no differences in vaginal microbiome composition between primiparous and multiparous sows, fecal microbiome composition was different (PERMANOVA, R 2 = 0.02, P = 0.03). The fecal microbiomes of primiparous offspring displayed significantly higher bacterial diversity compared with multiparous offspring at d0 and d21 (Shannon's H, P < 0.01), with differences in community composition observed at d21 only (PERMANOVA, R 2 = 0.03, P = 0.04). When analyzing the effects of maternal parity within each treatment, only the PRE diet showed significant compositional distinctions between primiparous and multiparous microbiomes (d21: PERMANOVA, R 2 = 0.13, P = 0.01; d42: PERMANOVA, R 2 = 0.19, P = 0.001). Compositional differences in pig fecal microbiomes between treatments, regardless of maternal parity, were observed only at d21 (PERMANOVA, R 2 = 0.12, P = 0.001). No significant differences in growth performance between treatment groups were observed. These results indicate that maternal parity influences pig gut microbiomes post-weaning, and may influence the effects of dietary prebiotics on nursery pig microbiomes.